Retellings : the Bible in literature, music, art and film - Exum, J. Cheryl. (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2007, ISBN: 9789004222700., 2007)
In recent years biblical scholars and students have become increasingly interested in studying retellings of biblical stories in the arts, not only for their relation to the biblical text but also for the 'story' they have to tell (or, if they are not strictly 'retellings', for the light they might shed on the biblical text). The eight lively contributions to this volume illustrate a range of exciting approaches to retellings of the Bible in literature, music, art and film and reveal something of the scope of this fascinating and rapidly expanding area of inquiry. The present collection of essays appears concurrently in a special issue of the journal Biblical Interpretation. Since it was founded in 1993, Biblical Interpretation has played a key role in fostering the publication of articles in the newly developing area of the reception history of the Bible in the arts. (Originally published as issue 4-5 of Volume 15 (2007) of Brill's journal Biblical Interpretation )